Synergistic enhancement of tendon-to-bone healing via anti-inflammatory and pro-differentiation effects caused by sustained release of Mg(2+)/curcumin from injectable self-healing hydrogels - Chen, Baojun (Theranostics, 2021)
Poor healing response after rotator cuff reconstruction is multifactorial, with the inflammatory microenvironment and deficiency of stem cell differentiation factors at the lesion site being most relevant. However, there is a lack of effective tissue engineering strategies that can simultaneously exert anti-inflammatory and pro-differentiation effects to promote rotator cuff healing. Methods: In this study, we synthesized and characterized a novel active drug delivery vector that successfully overcame the challenge of simultaneous high-efficiency loading and controlled release of Mg(2+) and curcumin. The anti-inflammatory and pro-differentiation effects of the composite hydrogel were evaluated in vitro and in vivo. Moreover, healing of the rotator cuff tendon-to-bone interface was studied by histology, immunofluorescence, and biomechanical tests. Results: The composite hydrogel exhibited excellent biocompatibility and injectability, good adhesiveness, and rapid self-healing. The released curcumin showed obvious anti-inflammatory and antioxidation effects, which protected stem cells and tendon matrix. Furthermore, released Mg(2+) promoted stem cell aggregation and chondrogenesis. Moreover, biomechanical tests and histological results of a rat rotator cuff tear model at 8 weeks after surgery indicated that the composite hydrogel significantly enhanced tendon-to-bone healing. Conclusions: The composite hydrogel mediated sustained in situ release of curcumin and Mg(2+) to effectively promote rotator cuff tendon-to-bone healing via anti-inflammatory and pro-differentiation effects. Therefore, this composite hydrogel offers significant promise for rotator cuff repair.